(untitled) (Sociología y Tecnociencia, 2013)
International mobility of the highly skilled has become one of the cornerstones of development in the current knowledge society. Correspondingly, highly skilled personnel are impelled to move abroad in order to improve their competences and build influential professional networks. Mobility implies some advantages involving personal, social and family opportunities when movers experience handicaps in their country of origin. For movers, mobility becomes a new challenge beyond the work-family balance, particularly for women who usually take on the lion’s share of childcare and domestic tasks within the family. The literature exploring the gender dimension in relation to international mobility points to complex outcomes. Firstly, women are taking on a more active role in international mobility processes, even when they have family. Secondly, family and international mobility are interrelated both for men and for women, although family could become a hindrance, particularly for women. Thirdly, international mobility and women’s career development may interfere with family formation or modify traditional family values. Finally, families moving abroad constitute a challenge for public policy, since they present a new area of problems. We aim to analyse the relationship between international mobility and family based on in-depth interviews from a purposive sample of highly skilled personnel in science and technology. The results of our research suggest that international mobility of the highly skilled has effects on the family and vice versa; however, while international mobility and family are compatible, measures and policies to reconcile them are still insufficient.